Diabetes self-management education interventions in the WHO African Region: A scoping review. - Emmanuel Kumah; Godfred Otchere; Samuel Egyakwa Ankomah; Adam Fusheini; Collins Kokuro; Kofi Aduo-Adjei; Joseph A Amankwah (PLoS ONE)
Introduction Diabetes mellitus (DM) is one of the commonest chronic diseases worldwide. Self-Management Education (SME) is regarded as a critical element of treatment for all people with diabetes, as well as those at risk of developing the condition. While a great variety of diabetes self-management education (DSME) interventions are available in high-income countries, limited information exists on educational programs for the prevention and management of diabetes complications in Africa. This study, therefore, aimed at synthesizing information in the literature to describe the state of the science of DSME interventions in the WHO African Region. Materials and methods The study is a scoping review, which followed the standard PRISMA guidelines for conducting and reporting scoping reviews. A systematic keyword and subject headings searches were conducted on six electronic databases (PubMed, Scopus, MEDLINE, EMBASE, PsychINFO and the Cochrane Central Register of Controlled Trials) to identify relevant English language publications on DSME from 2000 through 2020. Titles and abstracts of the search results were screened to select eligible papers for full text reading. All eligible papers were retrieved and full text screening was done by three independent reviewers to select studies for inclusion in the final analysis. Results Nineteen studies were included in the review. The interventions identified were individually oriented, group-based, individually oriented & group-based, and information technology-based DSME programs. Outcomes of the interventions were mixed. While the majority yielded significant positive results on HbA1c, diabetes knowledge, blood pressure, blood sugar and foot care practices; few demonstrated positive outcomes on self-efficacy, BMI, physical activity; self-monitoring of blood glucose, medication adherence, smoking and alcohol consumption. Conclusions The limited studies available indicate that DSME interventions in the WHO African Region have mixed effects on patient behaviors and health outcomes. That notwithstanding, the majority of the interventions demonstrated statistically significant positive effects on HbA1c, the main outcome measure in most DSME intervention studies.